Sex-specific associations with youth obesity in Queensland, Australia. (April 2017) - Miura, K.; Ballard, E.; Clemens, Susan L.; Harper, C.M.; Begum, N.; O'Rourke, P.K.; Green, A.C.
Highlights: In Queensland, Australia, 1 in 10 youth aged 5–17 years are obese. Obesity in adolescent girls but not boys is strongly associated with parents' education and marital status. Obesity in boys is more strongly associated with take-away food consumption than in girls.